A Girl with Ulcerative Colitis in a Tertiary Care Hospital- a Case Report - Nahar, N; Sultana, S; Chowdhury, MLL; Chowdhury, K (Pulse, 2014)
Ulcerative colitis (UC) is a chronic idiopathic inflammatory disorder of colon. We are presenting a case of ulcerative colitis in a 12 yrs old girl who presented with passage of loose bloody stool, low grade intermittent fever, abdominal pain with tenesmus and arthralgia of large joint along with significant wt loss. Diagnosis was confirmed by colonoscopy and biopsy. Treatment was thereafter started with parenteral steroid initially then oral steroid and meselamine. The patient is now on remission and is on regular follow up. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20352 Pulse Vol.6 January-December 2013 p.53-56